IMPLEMENTATION OF HYBRID CONTRACTS CONCEPT OF SHARIA PAWN IN SHARIA BANKING - Suhendar, Heris (Journal of Economicate Studies, 2017)
The existence of people's need for financing is fast, easy, safe and certainly in accordance with the principles of sharia, triggering sharia banking to innovate. One form of innovation issued by sharia banks to support the needs of the community is the product of pawn gold sharia. On the other hand, concerns arise about the product of rahn (sharia pawn), because the rahn product (gold pawn) is not a productive asset in the profit. Considerations arise when the profits are derived from the percentage of the loan amounts given by the bank to customers, as is the practice in conventional banking. Based on the problems that will be examined by the author above, then the method used in the research is normative legal research method. The results of the research are: 1) gold pawning products performed by sharia banks using three contracts, namely contracts qardh, rahn, and ijarah; 2) the amount or amount of the place rental charge shall not be calculated from the percentage of the loan or the loan granted by the bank to the customer, but the amount of the fee is taken from the expenses that are clearly required; And 3) when payment is due, then the customer could not repay the debt, it shall be returned to the agreement which has been made and agreed by the parties.